PENGARUH PEWARNAAN LAMPU TERHADAP PERFORMA AYAM FASE LAYER PADA SISTEM KANDANG CLOSED HOUSE - Ike Septa Krisnawati; Efi Rokana; Ertika Fitri Lisnanti (Universitas Islam Kadiri, 2018)
Enclosure is one of the success factors in a poultry farm. Closed house enclosure is a modern enclosure that has many advantages ranging from labor efficiency, temperature and humidity that can be adjusted, without being affected by the temperature from outside the enclosure. The purpose of this study was to determine the effect of lamp coloring on the performance of the chicken phase layer in the closed house cage system. The study was conducted in July 2018 on the farm owned by Mr. Rudyanto Margadji located in Balapan Village, Sukorejo District, Blitar Regency. Data obtained from farms is processed using unpaired t test. The variables observed included feed consumption (feed intake), daily egg production (Hen day), feed conversion (FCR). The results showed that the level of consumption of feed on red lights averaged = 120.3 g, whereas for yellow lights = 120.2 g, for Hen Day on average = 92.33% for red lights and for yellow lights = 86.22%. The FCR value at the red light indicates an average of 2.04 and for the yellow light is 2.13.